ANALISIS EVALUASI PEMBELAJARAN IPAS MI/SD DALAM MENCAPAI TUJUAN KURIKULUM MERDEKA - Nur Fitri Amalia; Farich Purwanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the evaluation of Integreted (IPAS) learning in elementary schools (MI/SD) in supporting the achievement of the goals of the Independent Curriculum. The Independent Curriculum emphasizes formative, holistic, authentic, and student-centered learning evaluation. This research approach utilizes a qualitative approach with literature study methods and descriptive analysis of the practice of evaluating Islamic studies (IPAS) learning in elementary schools (MI/SD). Data collection techniques include literature review, document analysis, and teacher reflection on learning evaluations. The results indicate that the implementation of Islamic studies (IPAS) learning evaluation in elementary schools (MI/SD) is still not fully aligned with the principles of the Independent Curriculum. School practice of learning evaluation is still dominated by summative assessments that focus on cognitive aspects, while assessments of attitudes and skills are suboptimal and poorly documented. Key inhibiting factors include teachers' limited understanding of authentic assessment, administrative burdens, and minimal school system support. This study concludes that strengthening teacher competencies and instructional support is necessary so that Islamic studies (IPAS) learning evaluation in elementary schools can contribute effectively to achieving the goals of the Independent Curriculum.